PENGARUH KEPERCAYAAN DIRI DAN ORIENTASI TUJUAN TERHADAP KINERJA KARYAWAN DI BSI KCP. PINRANG - Rahman, Resty (Funds: Jurnal Ilmiah Akuntansi, Keuangan, dan Bisnis, 2024)
The morefierce competition in the business world, organizations or companies are required to be efficient and competitive in meeting public needs. In the era of globalization itself, competition for human resources is getting tougher. As a result, human resources must develop their potential. The purpose of this study is to (1) determine whether there is a significant effect of Self efficacy on employee performance (2) determine whether there is a significant effect of Goal orientation on employee performance (3) determine whether there is a simultaneous effect of Self efficacy and Goal orientation on employee performance. In this study, the Quantitative method is used with three types of approaches, namely descriptive approach, verification approach & causal approach. Data collection techniques using primary and secondary data with research instruments using questionnaires and documentation. Data analysis using Multiple Linear Regression Analysis which was analyzed from a questionnaire with the help of the SPSS program and Microsoft Excel. The results showed that (1) the individual test (t test), titung 1957.829> t table 2.228, the significance level of Self efficacy 0.000 < α 0.05 thus Self efficacy has a significant effect on employee performance at BSI Pinrang. (2) Goal orientation t test produces a tcount value of 43.703> t table 2.228 and a significance value of 0.000 < α 0.05 thus Goal orientation significantly affects employee performance at BSI KCP.Pinrang. (3) From the results of 127 simultaneous test calculation tests (f test), F41 count = 17.973> Ftable 3.98 and a significant value of 0.000 < α 0.05 which means there is a significant influence between Self efficacy (X1) and Goal orientation (X2) on Employee Performance ((Y). (4) from the results of multiple linear regression analysis, the regression coefficient of Self efficacy is 0.888 and the regression coefficient of Goal orientation102 is 0.119, which means that Self efficacy is more dominant in influencing employee performance. The results also show that both have a strong and significant correlation with employee performance, with a coefficient of determination of 73.9%.